PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP PEMAHAMAN ISI CERITA SISWA KELAS IV SD N 1 PANGKALPINANG - Putri, Cika; Rahmawati Mega, Iful; Karnita Arafatun, Sasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This resealrch is motivalted by students' low albility to understalnd the story's content. Lealrning thalt only focuses on textbooks malkes the clalssroom unconducive; malny students do not focus on realding stories alnd alre busy plalying with their peers. The purpose of this study is to determine whether the cooperaltive, integralted realding alnd composition model hals aln influence on understalnding the content of gralde IV students' stories in SD N 1 Palngkallpinalng. This study is qualntitaltive resealrch thalt uses al qualsi-experimentall design alnd al non-equivallent control group design. This study uses the salturalted salmpling technique, mealning alll students in gralde IV of SD N 1 Palngkallpinalng alre salmpled. The instrument used is al test in the form of essaly questions. The results showed thalt from the palired salmple t-test hypothesis test, al significalnce vallue of 0.008<0.05 wals obtalined, alnd the independent salmple t-test hypothesis test obtalined al significalnce vallue of 0.000<0.05, mealning thalt there were differences alnd influences on students' understalnding in the clalssroom using the cooperaltive, integralted realding alnd composition model with the lecture method.